Developing 'I Can Adapt' Science Module Using RIAS Learning for Enhanced Critical Thinking - Dwi Rahayu; Ahmad Muhlisin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
In the context of Natural Science lessons, students often lack critical thinking skills. To address this challenge, the researchers developed the “I Can Adapt” scientific module for students at SMP Negeri 10 Magelang. This study evaluates the module’s viability, efficacy, and practicality using a research and development (R&D) approach based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The expert validation process confirmed the module’s validity, with material experts rating it at 4.0 and teaching materials experts at 4.2. To assess efficacy, the researchers employed a one-group pretest-posttest design with paired sample t-test analysis. The results revealed a significant increase in critical thinking skills (p < 0.05), as indicated by a significance value of 0.00. The average N-Gain score of 0.83 falls within the high category. Furthermore, student questionnaires related to the RIAS-based science modules demonstrated a practicality level of 84.6%. Overall, the findings support the use of the “I Can Adapt” RIAS-based science module as an effective tool for enhancing critical thinking abilities.